Toughened polyamide 66 composite material and preparation method thereof
By adding homemade toughening agent and silicone flow modifier to polyamide 66, the brittleness and fluidity problems under low temperature and high impact conditions are solved, and the toughening and fluidity of the material is improved while maintaining the Other excellent performance.
Patent Information
- Application Number
- CN202510018527.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polyamide 66 is highly brittle and has poor fluidity under low temperature or high impact load conditions, resulting in limited application. The addition of existing toughening agents and flow agents will affect its other properties.
By selecting homemade toughening agents and silicone flow modifiers, polyamide 66 is toughened and flow-modified, and a composite material with good toughness and flow under low temperature and high impact load conditions was prepared. .
The toughening and fluidity improvement of polyamide 66 composite material is achieved, maintaining its other properties, such as heat resistance and mechanical strength, suitable for extremely cold environments and parts requiring high flow and rapid molding.
Smart Images

Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a toughened polyamide 66 composite material and a preparation method thereof. Background Art
[0002] Polyamide 66 (PA66) is an engineering plastic widely used in the industrial field. It is widely used in the fields of automobiles, electronic appliances, mechanical equipment manufacturing, etc. due to its excellent mechanical properties, heat resistance, chemical resistance and processing performance. However, the brittleness and poor fluidity of polyamide 66 under low temperature or high impact load conditions limit its application. In order to overcome this defect, it is usually necessary to add toughening agents and flow agents to improve its toughness, reduce brittleness and increase fluidity. The addition of traditional toughening agents and flow agents will affect other properties of polyamide 66, such as heat resistance, mechanical strength and other properties. Therefore, it is of great practical significance to develop a polyamide 66 composite material that can effectively toughen and improve fluidity without compromising other properties. Summary of the invention
[0003] In view of the problems existing in the prior art, the present invention toughens and modifies the fluidity of the polyamide 66 composite material by selecting a homemade toughening agent and an organosilicon flow modifier, thereby obtaining a polyamide 66 composite material with good toughness and good fluidity under low temperature and high impact load conditions. The toughened polyamide 66 composite material provided in the present invention can be used for components such as cable ties, buckles, wire ducts, pipe clamps, etc. in electric vehicles or industrial equipment in extremely cold environments, and is particularly suitable for components that require high fluidity and rapid prototyping. The present invention provides a toughened polyamide 66 composite material, which includes the following components by weight: Polyamide 66 86-95 parts; 5-10 parts of toughening agent; Flow modifier 0.5-2 parts; Antioxidant 0.25-0.75 parts; Lubricant 0.25-0.5 parts; Black masterbatch 0.5-2 parts; The relative viscosity of the polyamide 66 is 2.0-4.0, and the flow modifier is a silicone flow modifier.
[0004] As a preferred technical solution, the polyamide 66 is a high molecular polymer obtained by copolymerization of adipic acid and hexamethylenediamine, and has the following structural formula (I): (I).
[0005] As a preferred technical solution, the relative viscosity of the polyamide 66 is one of 2.0, 2.4, 2.7, 3.0, 3.2, and 4.0.
[0006] As a preferred technical solution, the relative viscosity of the polyamide 66 is 3.2.
[0007] The relative viscosity in the present invention is tested with reference to the test standard of ISO 307.
[0008] 3.2 viscosity is high viscosity. Compared with medium and low viscosity, it has higher impact performance in toughened polyamide 66, while compared with ultra-high viscosity, it retains appropriate fluidity.
[0009] As a preferred technical solution, the polyamide 66 brand is preferably Henan Shenma EPR32, Huafeng T31 or Radici A75. Referring to the test standard of ISO 307, the relative viscosity of Henan Shenma EPR32, Huafeng T31 and Radici A75 is 3.2. Referring to the test standard of ISO 307, the relative viscosity of PA66 brand Shenma EPR27 is 2.7, and the relative viscosity of PA66 brand Huafeng PA66 T37 is 3.7.
[0010] As a preferred technical solution, the toughening agent is at least one of maleic anhydride grafted polyolefin elastomer (POE-g-MAH), maleic anhydride grafted ethylene propylene rubber (EPDM-g-MAH), hydrogenated styrene-butadiene block copolymer (Ethylene acrylate copolymer), ethylene-acrylate copolymer (Ethylene Propylene Acrylate), ethylene-methacrylic acid copolymer (Ethylene-Methacrylic Acid), and ethylene-vinyl acetate copolymer (EVA).
[0011] As a preferred technical solution, the toughening agent is maleic anhydride grafted polyolefin elastomer (POE-g-MAH), and the preparation method of the maleic anhydride grafted polyolefin elastomer comprises at least the following steps: First, 1wt% of maleic anhydride (MAH), 0.2wt% of initiator dicumyl peroxide (DCP) and 0.1wt% of antioxidant 1010 are dissolved in acetone to obtain a mixed solution, and then the mixed solution is introduced into a polyolefin elastomer and mixed evenly. After the acetone is volatilized, the mixed solution is introduced into a twin-screw extruder, melt-extruded, and water-cooled and pelletized to obtain a maleic anhydride grafted polyolefin elastomer (POE-g-MAH). The weight percentages of the maleic anhydride, the initiator dicumyl peroxide and the antioxidant 1010 are calculated based on the weight of the polyolefin elastomer.
[0012] As a preferred technical solution, the glass transition temperature (Tg) of the polyolefin elastomer is -62°C.
[0013] The inventors found that a polyolefin elastomer with a glass transition temperature of -62°C was selected to prepare a toughening agent, and the toughening agent had good low-temperature toughness.
[0014] As a preferred technical solution, the screw length-to-diameter ratio of the twin-screw extruder is 40:1, and the temperatures of the barrel in each stage are: 40°C, 190°C, 190°C, 190°C, 190°C, 160°C, 130°C, 130°C, 130°C, 190°C, the head is 200°C, and the screw speed is 350rpm-450rpm.
[0015] As a preferred technical solution, the grade of the polyolefin elastomer is POE engage-11547, and the glass transition temperature is -62°C.
[0016] As a preferred technical solution, the flow modifier is a silicone flow modifier.
[0017] More preferably, the brand of the silicone flow modifier is Jiayirong EMI-150C.
[0018] The inventors have found that the performance of the composite material prepared by using an organosilicon flow modifier is better than that prepared by using a hyperbranched polymer flow modifier (such as the brand Wuhan Hyperbranched Hyper C100, Wuhan Hyperbranched HyPerC181).
[0019] As a preferred technical solution, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 1024, antioxidant 445, antioxidant 264, antioxidant 168, antioxidant 626, and antioxidant 9228.
[0020] As a preferred technical solution, the antioxidant is a mixture of antioxidant 1098 and antioxidant 9228, and the mass ratio of the antioxidant 1098 to the antioxidant 9228 is 1:1.
[0021] Antioxidant 1098 belongs to the hindered phenol antioxidant class, while antioxidant 9228 is a phosphite antioxidant. When these two different types of antioxidants are compounded, the highly active antioxidant can capture free radicals and terminate the active chain reaction, while the low-activity antioxidant can provide highly active hydrogen atoms to recombine the antioxidant molecules. As the main antioxidant, antioxidant 1098 has good processing stability and long-term thermal stability. As a secondary antioxidant, antioxidant 9228, when used in conjunction with the main antioxidant, can be processed stably and effectively, and improve antioxidant performance. Especially in high-temperature processing and application processes, antioxidants can provide good high-temperature degradation protection.
[0022] As a preferred technical solution, the lubricant is at least one of N,N-ethylene bisstearamide, polyethylene wax, silicone, pentaerythritol stearate, calcium stearate, zinc stearate, montan wax, rice bran wax, silicone oil, and ethylene acrylic acid copolymer.
[0023] As a preferred technical solution, the lubricant is ethylene acrylic acid copolymer.
[0024] As a preferred technical solution, the brand of the ethylene acrylic acid copolymer is Honeywell's AC540A.
[0025] Ethylene acrylic acid copolymer is an excellent lubricant for polyamide 66, has a good demoulding effect, does not affect the notched impact performance of the material in the toughened nylon system, reduces mold pressure and melt temperature, and improves the fluidity of the material.
[0026] As a preferred technical solution, the brand of the black masterbatch is selected from at least one of Colloids N54 / 1033, Cabot UN2014, Cabot UN2005, Cabot UN6073, and Cabot XP6585B.
[0027] As a preferred technical solution, the brand of the black masterbatch is Cabot UN2014.
[0028] Another aspect of the present invention provides a method for preparing the toughened polyamide 66 composite material, comprising at least the following steps: Polyamide 66 is mixed with a toughening agent, a flow modifier, an antioxidant, a lubricant and a black masterbatch and then extruded in a twin-screw extruder to obtain a toughened polyamide 66 composite material.
[0029] As a preferred technical solution, in the method for preparing the toughened polyamide 66 composite material, the screw aspect ratio of the twin-screw extruder is (40-48):1, the barrel temperature is 260°C-300°C, and the screw speed is 450rpm-550rpm.
[0030] Beneficial Effects
[0031] The present invention can effectively improve the toughening performance of the polyamide 66 composite material by adding a low amount of toughening agent, and the material has good low-temperature toughness and fluidity. By adding a suitable flow modifier, the impact performance of the material is not affected, and the composite material has good fluidity. The toughened PA66 composite material of the present invention has good processability, good thermal stability, low-temperature impact resistance, simple material preparation process, low cost, and can be used for applications such as cable ties, buckles, wire ducts, and pipe clamps on electric vehicles or industrial equipment in extremely cold environments. DETAILED DESCRIPTION
[0032] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0033] The specific implementation method of the present invention provides a toughened polyamide 66 composite material, which includes the following components in parts by weight: Polyamide 66 86-95 parts; 5-10 parts of toughening agent; Flow modifier 0.5-2 parts; Antioxidant 0.25-0.75 parts; Lubricant 0.25-0.5 parts; Black masterbatch 0.5-2 parts; The relative viscosity of the polyamide 66 is 2.0-4.0, and the flow modifier is a silicone flow modifier.
[0034] Among them, the weight of polyamide 66 can be 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts, 94 parts or 95 parts, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. The weight of the toughening agent can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. The weight of the flow modifier can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 2 parts, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. The weight portion of the antioxidant can be 0.3, 0.4, 0.5, 0.6, or 0.7, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable. The weight portion of the lubricant can be 0.3 or 0.4, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable. The weight portion of the black masterbatch can be 0.6, 0.7, 0.8, 0.9, or 2, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0035] As a preferred technical solution, the polyamide 66 is a high molecular polymer obtained by copolymerization of adipic acid and hexamethylenediamine, and has the following structural formula (I): (I).
[0036] As a preferred technical solution, the relative viscosity of the polyamide 66 is at least one of 2.0, 2.4, 2.7, 3.0, 3.2, and 4.0.
[0037] As a preferred technical solution, the relative viscosity of the polyamide 66 is 3.2.
[0038] The relative viscosity in the present invention is tested with reference to the test standard of ISO 307.
[0039] 3.2 viscosity is high viscosity. Compared with medium and low viscosity, it has higher impact performance in toughened polyamide 66, while compared with ultra-high viscosity, it retains appropriate fluidity.
[0040] As a preferred technical solution, the polyamide 66 brand is preferably Henan Shenma EPR32, Huafeng T31 or Lantici A75. Referring to the test standard of ISO 307, the relative viscosity of Henan Shenma EPR32, Huafeng T31 and Lantici A75 is 3.2.
[0041] As a preferred technical solution, the toughening agent is at least one of maleic anhydride grafted polyolefin elastomer (POE-g-MAH), maleic anhydride grafted ethylene propylene rubber (EPDM-g-MAH), hydrogenated styrene-butadiene block copolymer (Ethylene acrylate copolymer), ethylene-acrylate copolymer (Ethylene Propylene Acrylate), ethylene-methacrylic acid copolymer (Ethylene-Methacrylic Acid), and ethylene-vinyl acetate copolymer (EVA).
[0042] As a preferred technical solution, the toughening agent is a maleic anhydride grafted polyolefin elastomer, and the preparation method of the maleic anhydride grafted polyolefin elastomer comprises at least the following steps: First, 1wt% of maleic anhydride (MAH), 0.2wt% of initiator dicumyl peroxide (DCP) and 0.1wt% of antioxidant 1010 are dissolved in acetone to obtain a mixed solution, and then the mixed solution is introduced into a polyolefin elastomer and mixed evenly. After the acetone is volatilized, the mixed solution is introduced into a twin-screw extruder, melt-extruded, and water-cooled and pelletized to obtain the obtained product. The weight percentages of the maleic anhydride, the initiator dicumyl peroxide and the antioxidant 1010 are calculated based on the weight of the polyolefin elastomer.
[0043] As a preferred technical solution, the glass transition temperature of the polyolefin elastomer is -62°C.
[0044] As a preferred technical solution, the screw length-to-diameter ratio of the twin-screw extruder is 40:1, and the temperatures of the barrel in each stage are: 40°C, 190°C, 190°C, 190°C, 190°C, 160°C, 130°C, 130°C, 130°C, 190°C, the head is 200°C, and the screw speed is 350rpm-450rpm.
[0045] As a preferred technical solution, the grade of the polyolefin elastomer is POE engage-11547, and the glass transition temperature is -62°C.
[0046] As a preferred technical solution, the flow modifier is a silicone flow modifier.
[0047] More preferably, the brand of the silicone flow modifier is Jiayirong EMI-150C.
[0048] As a preferred technical solution, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 1024, antioxidant 445, antioxidant 264, antioxidant 168, antioxidant 626, and antioxidant 9228.
[0049] As a preferred technical solution, the antioxidant is a mixture of antioxidant 1098 and antioxidant 9228, and the mass ratio of the antioxidant 1098 to the antioxidant 9228 is 1:1.
[0050] As a preferred technical solution, the lubricant is at least one of N,N-ethylene bisstearamide, polyethylene wax, silicone, pentaerythritol stearate, calcium stearate, zinc stearate, montan wax, rice bran wax, silicone oil, and ethylene acrylic acid copolymer.
[0051] As a preferred technical solution, the lubricant is ethylene acrylic acid copolymer.
[0052] As a preferred technical solution, the brand of the ethylene acrylic acid copolymer is Honeywell's AC540A.
[0053] Ethylene acrylic acid copolymer is an excellent lubricant for polyamide 66, has a good demoulding effect, does not affect the notched impact performance of the material in the toughened nylon system, reduces mold pressure and melt temperature, and improves the fluidity of the material.
[0054] As a preferred technical solution, the brand of the black masterbatch is selected from at least one of Colloids N54 / 1033, Cabot UN2014, Cabot UN2005, Cabot UN6073, and Cabot XP6585B.
[0055] As a preferred technical solution, the brand of the black masterbatch is Cabot UN2014.
[0056] Another aspect of the present invention provides a method for preparing the toughened polyamide 66 composite material, comprising at least the following steps: Polyamide 66 is mixed with a toughening agent, a flow modifier, an antioxidant, a lubricant and a black masterbatch and then extruded in a twin-screw extruder to obtain a toughened polyamide 66 composite material.
[0057] As a preferred technical solution, in the method for preparing the toughened polyamide 66 composite material, the screw aspect ratio of the twin-screw extruder is (40-48):1, the barrel temperature is 260°C-300°C, and the screw speed is 450rpm-550rpm.
[0058] As a preferred technical solution, in the preparation method of the toughened polyamide 66 composite material, the screw aspect ratio of the twin-screw extruder is (40-48):1, for example, 40:1, 44:1 or 48:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; the barrel temperature is 260°C-300°C, for example, 260°C, 270°C, 280°C, 290°C or 300°C, and is not limited to the listed values, and other unlisted values within the numerical range are also applicable; the screw speed is 450rpm-550rpm, for example, 450rpm, 470rpm, 490rpm, 510rpm, 530rpm or 550rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] The following are typical but non-limiting embodiments of the present invention: Embodiment 1-3:
[0060] The composition of the formulation materials in Examples 1-3 is specifically shown in Table 1 below. The preparation methods of the toughened polyamide 66 composite materials provided in Examples 1-3 are the same, specifically as follows: (1) First, 1 wt% of maleic anhydride (MAH), 0.2 wt% of initiator dicumyl peroxide (DCP), and 0.1 wt% of antioxidant 1010 are dissolved in acetone (the weight percentages of maleic anhydride, initiator dicumyl peroxide, and antioxidant 1010 are calculated based on the weight of the polyolefin elastomer) to prepare a mixed solution, and the solution is introduced into the polyolefin elastomer (the grade of the polyolefin elastomer is POE engage-11547) and mixed evenly. After the acetone evaporates, the mixture is introduced into the feed port of a twin-screw extruder. The screw aspect ratio of the twin-screw extruder is 40:1. The temperatures of the barrels at each stage are: 40°C, 190°C, 190°C, 190°C, 190°C, 160°C, 130°C, 130°C, 130°C, 190°C, the die is 200°C, the screw speed is 400rpm, and the pelletizing is carried out under water cooling to obtain homemade POE-g-MAH-1. (2) Weigh all the raw materials according to the material proportions of Examples 1 to 3 in Table 1 and put them into a high-speed mixer for stirring to obtain a premix; (3) The premix obtained in step (2) is put into a twin-screw extruder for melt mixing, and extruded into granules to obtain a toughened polyamide 66 composite masterbatch, wherein the screw aspect ratio of the twin-screw extruder is 44:1, the barrel temperature is 280°C, 280°C, 280°C, 280°C, 270°C, 270°C, 270°C, 270°C, 270°C, the die temperature is 280°C, and the screw speed is 500 rpm.
[0061] Comparative Examples 1-8:
[0062] The composition of the formulation materials in Comparative Examples 1-8 is specifically shown in Table 1 below. The preparation methods of the toughened polyamide 66 composite materials provided in Comparative Examples 1-8 are the same, specifically as follows: (1) All raw materials were weighed according to the proportions of the comparative examples in Table 1 and put into a high-speed mixer for stirring to obtain a premix; wherein the preparation method of the toughening agent in comparative example 5 is as follows: first, 1wt% maleic anhydride (MAH), 0.2wt% initiator dicumyl peroxide (DCP) and 0.1wt% antioxidant 1010 were dissolved in acetone (the weight percentages of the maleic anhydride, the initiator dicumyl peroxide and the antioxidant 1010 were calculated based on the weight of the polyolefin elastomer) to prepare a mixed solution, and the solution was introduced into the polyolefin elastomer (the grade of the polyolefin elastomer was POE engage-8150, the glass transition temperature Tg of POEengage-8150 is -52°C) and mixed evenly, after the acetone is volatilized, the mixture is introduced into the material port of a twin-screw extruder, the screw aspect ratio of the twin-screw extruder is 40:1, the temperatures of the barrels at each stage are: 40°C, 190°C, 190°C, 190°C, 190°C, 160°C, 130°C, 130°C, 130°C, 190°C, the die is 200°C, the screw speed is 400rpm, and the pelletizing is water-cooled to obtain homemade POE-g-MAH-2; (2) The premix obtained in step (1) is put into a twin-screw extruder for melt mixing, and extruded into granules to obtain a toughened polyamide 66 composite masterbatch, wherein the screw aspect ratio of the twin-screw extruder is 44:1, the barrel temperature is 280°C, 280°C, 280°C, 280°C, 270°C, 270°C, 270°C, 270°C, 270°C, the die temperature is 280°C, and the screw speed is 500 rpm.
[0063] Table 1 - Formula materials used in Examples 1-3 and Comparative Examples 1-8
[0064] The toughened polyamide 66 composite materials in Examples 1-3 and Comparative Examples 1-8 were tested in the following specific methods: The toughened polyamide 66 composite masterbatch prepared in each embodiment and each comparative example was dried in a blast oven at 120°C for 4 hours and then injection molded into a standard specimen using a plastic injection molding machine, and the injection molding temperature was 275±15°C. The injection molded specimen was immediately placed in a glass dryer and placed at room temperature for 24 hours before the performance test. The tensile strength and elongation at break were tested using the "Test Method for Tensile Properties of Plastics" (ISO 527-2), and the 23°C / -40°C Simple Supported Beam Notch Impact Test was performed using the "Determination of Impact Properties of Plastics-Simple Supported Beam" (ISO 179), and the pendulum used was 4J. The fluidity is characterized by the injection molding spiral flow length ratio under the same process conditions, that is, a scale is engraved on the mold. Under the same process conditions, the flow length of the composite material in the mold is the spiral flow length ratio, and materials with good fluidity have a larger spiral flow length ratio.
[0065] The test results of the polyamide 66 composite materials in Examples 1-3 and Comparative Examples 1-8 are shown in Table 2.
[0066] Table 2 - Test results of Examples 1-3 and Comparative Examples 1-8
[0067] It can be seen from the test results that the present invention can effectively improve the fluidity, toughness and low-temperature impact performance of polyamide 66 composite materials by adding a homemade POE-g-MAH toughening agent and flow modifier with a low glass transition temperature (Tg) to polyamide 66 with a viscosity of 3.2, so that the elongation at break of the material reaches more than 20%, the low-temperature impact of the -40℃ simply supported beam notched impact is more than 10 kJ / ㎡, and the spiral flow length is also improved. Selecting low-Tg (-62℃) POE as the toughening agent substrate in the homemade toughening agent has a better effect under low-temperature impact than POE with Tg (-52℃). The viscosity of polyamide 66 is related to its molecular weight and molecular structure. Generally speaking, polyamide 66 with a higher viscosity has a higher molecular weight, which means a longer molecular chain. Longer molecular chains can provide more entanglement points and intermolecular interactions, which helps to disperse and absorb energy when impacted, thereby improving the toughness of the material. However, the fluidity drops sharply under high viscosity, and a higher processing temperature is required to achieve good fluidity. Thermal decomposition may occur at high processing temperatures, affecting product quality and performance. Due to the poor fluidity of high-viscosity polyamide 66, the injection molding cycle will be extended, thereby reducing production efficiency. High-viscosity polyamide 66 may also cause uneven filling of the molten material in the mold, causing defects in the internal structure of the product, such as bubbles, shrinkage holes and weld lines. The addition of conventional flow modifiers on the market has significantly improved fluidity, but it can be seen that the impact performance has significantly decreased. The flow modifier may cause changes in the microstructure of the material, and the interaction between polyamide molecular chains, such as hydrogen bonds, will weaken the connection between polymer chains, reduce the toughness of the material, and thus reduce the impact strength of the material. Some flow modifiers may reduce the molecular weight of polyamide through chemical or mechanical effects, resulting in a decrease in the mechanical properties of the material. The inventors found that by selecting a silicone flow modifier with a specific structure, the fluidity of polyamide 66 with a viscosity of 3.2 was improved while having no significant effect on the room temperature and low temperature impact properties of the polyamide composite material.
[0068] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A toughened polyamide 66 composite material, characterized in that: The following components are included by weight: Polyamide 66 86-95 parts; 5-10 parts of toughening agent; Flow modifier 0.5-2 parts; Antioxidant 0.25-0.75 parts; Lubricant 0.25-0.5 parts; Black masterbatch 0.5-2 parts; The relative viscosity of the polyamide 66 is 2.0-4.0, and the flow modifier is a silicone flow modifier.
2. The toughened polyamide 66 composite material according to claim 1, characterized in that: The relative viscosity of the polyamide 66 is 3.
2.
3. The toughened polyamide 66 composite material according to claim 2, characterized in that: The toughening agent is at least one of maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted EPDM rubber, hydrogenated styrene-butadiene block copolymer, ethylene-acrylate copolymer, ethylene-methacrylic acid copolymer, and ethylene-vinyl acetate copolymer.
4. The toughened polyamide 66 composite material according to claim 3, characterized in that: The toughening agent is a maleic anhydride grafted polyolefin elastomer, and the preparation method of the maleic anhydride grafted polyolefin elastomer comprises at least the following steps: First, 1wt% of maleic anhydride, 0.2wt% of initiator dicumyl peroxide and 0.1wt% of antioxidant 1010 are dissolved in acetone to obtain a mixed solution, and then the mixed solution is introduced into a polyolefin elastomer and mixed evenly. After the acetone is volatilized, the mixed solution is introduced into a twin-screw extruder, melt-extruded, and water-cooled and pelletized to obtain a maleic anhydride grafted polyolefin elastomer. The weight percentages of the maleic anhydride, the initiator dicumyl peroxide and the antioxidant 1010 are calculated based on the weight of the polyolefin elastomer.
5. The toughened polyamide 66 composite material according to claim 4, characterized in that: The glass transition temperature of the polyolefin elastomer is -62°C.
6. The toughened polyamide 66 composite material according to claim 5, characterized in that: The antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 1024, antioxidant 445, antioxidant 264, antioxidant 168, antioxidant 626, and antioxidant 9228.
7. The toughened polyamide 66 composite material according to claim 6, characterized in that: The antioxidant is a mixture of antioxidant 1098 and antioxidant 9228, and the mass ratio of the antioxidant 1098 to the antioxidant 9228 is 1:
1.
8. The toughened polyamide 66 composite material according to claim 7, characterized in that: The lubricant is at least one of N,N-ethylene bisstearamide, polyethylene wax, silicone, pentaerythritol stearate, calcium stearate, zinc stearate, montan wax, rice bran wax, silicone oil, and ethylene acrylic acid copolymer.
9. The toughened polyamide 66 composite material according to claim 8, characterized in that: The lubricant is ethylene acrylic acid copolymer.
10. A method for preparing the toughened polyamide 66 composite material according to any one of claims 1 to 9, characterized in that: At least the following steps are included: Polyamide 66 is mixed with a toughening agent, a flow modifier, an antioxidant, a lubricant and a black masterbatch and then extruded in a twin-screw extruder to obtain a toughened polyamide 66 composite material.
Citation Information
Patent Citations
Polyamide toughening material and preparation method thereof
CN103951969A
Ultra-low temperature-resistant toughening material for injection molding-grade nylon and preparation method of toughening material
CN108129757A
Nylon composite material capable of tolerating alpine region impact, and preparation method thereof
CN109880360A
High toughness nylon material and preparation method thereof
CN110194894A
PA66 composite material and preparation method thereof and automobile regulator connecting piece
CN111117238A
Cited By
Low-density high-flexibility polyamide plastic and preparation method thereof
CN121293490A